ANALISIS POLA SEBARAN RITEL MODERN DI KOTA BANDA ACEH - Fatimah Zuhra; Vivi Silvia (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to analyze the factors that influence the decision making of modern retailers location and to find the distribution pattern of modern retail in Banda Aceh. Primary data obtained by questionnaire distribution techniques to retailers in Banda Aceh, as 64 retailers, while secondary data obtained from goverment agencies in Banda Aceh. This study uses two data analysis models, first, to look the factors that influence the decision of modern retail locations in Banda Aceh using factor analysis with SPSS, while to see the pattern of retail distribution using the analysis of the  nearest neighbor analysis. The results of this study reveal that demographic, socioeconomic, psychographic, accessibility, business competition and demand changes influence the decision on the choice of retail locations in Banda Aceh and the pattern of retail distribution in Banda Aceh tends to clust, which tends to approach road networks and tend to gather in the center of City. It is hoped that this research can manage the distribution of retail more evenly in various regions of Banda Aceh, by organizing the distance between retail, further developing retail in the periphery and creating a new growth center to solve competition in the city center.Keywords: Location, Distribution Pattern, Modern Retail, Factor Analysis, Nearest Neighbor Analysis